Exploring the Impact of Taxes, Firm Size and Bonus Mechanisms on Transfer Pricing Decisions - Hidayah, Nisa Ulil; Madjid, Suhirman (Santoso Academy Network, 2024)
This research examines the impact of tax variables, company size, and bonus mechanisms on corporate decisions to engage in transfer pricing. The study focuses on manufacturing companies listed on the Indonesia Stock Exchange (BEI) during the 2014–2016 period, with 34 firms selected using the purposive sampling method. Secondary data was analyzed using multiple linear regression with a 5% significance level, processed through SPSS v.20 software. Findings reveal that tax variables, company size, and bonus mechanisms positively influence transfer pricing decisions. This suggests that companies leverage these factors to optimize tax burdens while adhering to internal and external incentives. The managerial implications underscore the importance of understanding international tax structures and regulations to implement legal transfer pricing strategies effectively. This study contributes original insights by integrating the bonus mechanism as a key determinant in transfer pricing, highlighting how internal compensation influences managerial decisions. The use of purposive sampling and robust statistical methods provides actionable recommendations for both regulators and corporate management. These findings encourage balancing tax optimization with ethical and compliance considerations, ensuring sustainable and transparent transfer pricing practices.